Eclampsia: maternal and perinatal outcomes in a tertiary care centre - Mor, Sunita; Sirohiwal, Daya; Hooda, Reetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Eclampsia is a life threatening emergency that continues to be a major cause of maternal and perinatal mortality. The purpose of our study was to analyse the trend of eclampsia in a tertiary care teaching institute and to find out maternal and perinatal outcomes of eclampsia. Methods: A prospective study was undertaken in a tertiary care teaching institute over a period of one year. Patients of eclampsia were followed up with regard to the management and maternal and fetal morbidity and mortality. Data was recorded and analysed. Maternal outcome was measured in terms of mode of delivery, complications like pulmonary oedema, haematological disorders, renal failure, cerebral haemorrhage and maternal death. Perinatal outcome was noted in terms of prematurity, admission to NICU and neonatal deaths. Results: The incidence of antepartum eclampsia was 1.08%. High risk associated factors were primigravida, low maternal age (21-25 years), low socio-economic status, illiteracy and inadequate antenatal care. Caesarean section was the mode of delivery in 26 cases (52%). There was 4% maternal mortality & attributed to aspiration pneumonia and pulmonary oedema. Maternal Complications were observed in 38% cases, most common was status eclampticus (12%) followed by HELLP syndrome (6%). Prematurity complicated 48% pregnancies and SGA in 14%. Fourteen neonates were admitted in NICU and there were 4 neonatal deaths. Conclusions: Eclampsia is one of the important causes of maternal and perinatal morbidity and mortality due to lack of proper antenatal care, low socio-economic status and lack of education. Early attention and intensive management are essential for improving the maternal and fetal outcomes. Unless the social and educational status of women is uplifted and obstetric care is brought to the doorstep, no miracle can be expected.